Pairing as an instructional strategy to promote soft skills amongst clinical dental students - Abu Kasim, Noor Hayaty; Abu Kassim, N.L.; Razak, A.A.A.; Abdullah, H.; Bindal, P.; Che Ab Aziz, Zeti Adura; Sulaiman, E.; Farook, M.S.; Gonzalez, M.A.G.; Thong, Y.L.; Ahmad, N.A.; Naimie, Z.; et al. (2013)
Training dentists today is challenging as they are expected to provide a wide range of dental care. In the provision of good dental care, soft skills are equally important as clinical skills. Therefore in dental education the development of soft skills are of prime concern. This study sought to identify the development of soft skills when dental students are paired in their clinical training. In this perception study, four open-ended items were used to elicit students' feedback on the appropriateness of using clinical pairing as an instructional strategy to promote soft skills. The most frequently cited soft skills were teamwork (70%) and communication (25%) skills. However, both negative and positive behaviours were reported. As for critical thinking and problem solving skills, more positive behaviours were reported for abilities such as to explain, analyze, find ideas and alternative solutions, and make decisions. Leadership among peers was not evident as leading without legitimate authority could be a hindrance to its development. If clinical pairing is to be used as an effective instructional strategy to promote soft skills amongst students, clear guidelines need to be developed to prepare students to work in a dental team and the use of appropriate assessment tools can facilitate the development of these soft skills.